Determinants of Functional and Structural Properties of Large Arteries in Healthy Individuals - Tolezani,Elaine Cristina (2014)
Background: Changes in the properties of large arteries correlate with higher cardiovascular risk. Recent guidelines have included the assessment of those properties to detect subclinical disease. Establishing reference values for the assessment methods as well as determinants of the arterial parameters and their correlations in healthy individuals is important to stratify patients. Objective: To assess, in healthy adults, the distribution of the values of pulse wave velocity, diameter, intima-media thickness and relative distensibility of the carotid artery, in addition to assessing the demographic and clinical determinants of those parameters and their correlations. Methods: This study evaluated 210 individuals (54% women; mean age, 44 ± 13 years) with no evidence of cardiovascular disease. The carotid-femoral pulse wave velocity was measured with a Complior® device. The functional and structural properties of the carotid artery were assessed by using radiofrequency ultrasound. Results: The means of the following parameters were: pulse wave velocity, 8.7 ± 1.5 m/s; diameter, 6,707.9 ± 861.6 μm; intima-media thickness, 601 ± 131 μm; relative distensibility, 5.3 ± 2.1%. No significant difference related to sex or ethnicity was observed. On multiple linear logistic regression, the factors independently related to the vascular parameters were: pulse wave velocity, to age (p < 0.01) and triglycerides (p = 0.02); intima-media thickness, to age (p < 0.01); diameter, to creatinine (p = 0.03) and age (p = 0.02); relative distensibility, to age (p < 0.01) and systolic and diastolic blood pressures (p = 0.02 and p = 0.01, respectively). Pulse wave velocity showed a positive correlation with intima media thickness (p < 0.01) and with relative distensibility (p < 0.01), while diameter showed a positive correlation with distensibility (p = 0.03). Conclusion: In healthy individuals, age was the major factor related to aortic stiffness, while age and diastolic blood pressure related to the carotid functional measure. The carotid artery structure was directly related to aortic stiffness, which was inversely related to the carotid artery functional property.